2023
DOI: 10.3389/fgene.2023.1145769
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gene expression profiles during fed–fasted–refed state in mice

Abstract: Background: Regulation of nutrient status during fasting and refeeding plays an important role in maintaining metabolic homeostasis in the liver. Thus, we investigated the impact of the physiological Fed–Fast–Refed cycle on hepatic gene expression in nutrient-sensitive mice.Methods: We performed transcriptomic analysis of liver samples in fed, fasted and refed groups of mice. Through mRNA-sequencing (RNA-Seq) and miRNA-Seq, we compared fasted and fed states (fasted versus fed cohort) as well as refed and faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Strikingly, we also found that oscillatory fed-microRNAs, which inhibit the expression of catabolic genes and consequently enable fasted-refed transition, are expressed in anticipation during a starvation state (Maniyadath et al, 2019). Albeit parallel studies have also illustrated circadian dependence or rhythmicity in the expression of microRNAs across tissues, including the liver (Menet et al, 2012;Vollmers et al, 2012;Ji et al, 2023), whether fed-fast cycles contribute to miR biogenesis independently or cooperatively (with circadian inputs) remains unknown. In this context, we have delineated the causal upstream cues that dictate the anticipatory expression of hepatic fed-microRNAs, especially for let-7i, mir-204, mir-221, and mir-222, which not only displayed the most robust oscillation but also otherwise have been shown to be important for liver functions and hepatic cancers (Chen et al, 2014;Luo et al, 2017;Song et al, 2017b).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Strikingly, we also found that oscillatory fed-microRNAs, which inhibit the expression of catabolic genes and consequently enable fasted-refed transition, are expressed in anticipation during a starvation state (Maniyadath et al, 2019). Albeit parallel studies have also illustrated circadian dependence or rhythmicity in the expression of microRNAs across tissues, including the liver (Menet et al, 2012;Vollmers et al, 2012;Ji et al, 2023), whether fed-fast cycles contribute to miR biogenesis independently or cooperatively (with circadian inputs) remains unknown. In this context, we have delineated the causal upstream cues that dictate the anticipatory expression of hepatic fed-microRNAs, especially for let-7i, mir-204, mir-221, and mir-222, which not only displayed the most robust oscillation but also otherwise have been shown to be important for liver functions and hepatic cancers (Chen et al, 2014;Luo et al, 2017;Song et al, 2017b).…”
Section: Discussionmentioning
confidence: 79%
“…We and others have demonstrated the significant role of miR-mediated regulation of gene expression in orchestrating physiological responses including during fed-fast cycles (Hu et al, 2012;Rottiers and Näär, 2012;Maniyadath et al, 2019;LaPierre et al, 2022). In addition to specific miR signatures that are associated with fed and fasted states in the liver (Na et al, 2009;Vollmers et al, 2012;Ji et al, 2023), hepatic miRs have also been shown to impinge on distant organ systems (Sung, Kim and Jung, 2018;Liu et al, 2020;Ji et al, 2021). However, metabolic inputs/signals that are essential for miR-homeostasis, from biogenesis and processing to degradation and secretion, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, we also found that oscillatory-fed microRNAs, which inhibit the expression of catabolic genes and consequently enable fasted-refed transition, are expressed in anticipation during a starvation state ( Maniyadath et al, 2019 ). Albeit parallel studies have also illustrated circadian dependence or rhythmicity in the expression of microRNAs across tissues, including the liver ( Menet et al, 2012 ; Vollmers et al, 2012 ; Ji et al, 2023 ), whether fed-fast cycles contribute to miR biogenesis independently or cooperatively (with circadian inputs) remains unknown. In this context, we have delineated the causal upstream cues that dictate the anticipatory expression of hepatic fed microRNAs, especially for let-7i, mir-204, mir-221, and mir-222, which not only displayed the most robust oscillation but also otherwise have been shown to be important for liver functions and hepatic cancers ( Chen et al, 2014 ; Luo et al, 2017 ; Song et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated the significant role of miR-mediated regulation of gene expression in orchestrating physiological responses including during fed-fast cycles ( Hu et al, 2012 ; Rottiers & Näär, 2012 ; Maniyadath et al, 2019 ; LaPierre et al, 2022 ). In addition to specific miR signatures that are associated with fed and fasted states in the liver ( Na et al, 2009 ; Vollmers et al, 2012 ; Ji et al, 2023 ), hepatic miRs have also been shown to impinge on distant organ systems ( Sung et al, 2018 ; Liu et al, 2020 ; Ji et al, 2021 ). However, metabolic inputs/signals that are essential for miR homeostasis, from biogenesis and processing to degradation and secretion, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in gene expression and autophagy have been increasingly reported as key factors in the energy dynamics of hepatocytes during fasting and feeding [ 5 , 6 , 7 ]. A majority of analyses have been performed on liver samples taken several hours after refeeding [ 8 , 9 , 10 ], and there are few reports of responses immediately after refeeding. The regulation of intracellular metabolite levels (lactate, pyruvate, and ATP) in hepatocytes may play a role in the quick response to refeeding; however, the dynamics of these metabolites in hepatocytes during refeeding after fasting are not clear.…”
mentioning
confidence: 99%